The Peculiarities of Forming Ideas of Primary School Pupils about Mental and Spiritual Components of Health at the Lessons of «Fundamentals of Health» - Hanna Byhar (Pedagogical Discourse, 2015)
Based on the analyzed sources it has been determined that from the position of the above stated understanding of the phenomenon of human health the components of a healthy lifestyle include various elements related to all areas of health – physical, mental, social and spiritual.It has been generalized that the scope of mental health includes individual characteristics of mental processes and properties of people, such as excitement, emotion, sensitivity. Mental life consists of individual needs, interests, motivations, incentives, attitudes, goals, ideas, feelings and so on. All these factors determine the components and features of individual reactions to the same life situations, the likelihood of stress, affects. It has been determined that the spiritual health depends on the spiritual world of the individual, including the components of spiritual culture of mankind – education, science, art, religion, morality and ethics. The consciousness of people, their mentality, vital identity, relationship to the meaning of life, evaluation of implementation of their own abilities and opportunities in the context of their own ideals and vision – all this makes the state of mental health of the individual.It has been concluded that in reality all four components – social, spiritual, physical, mental act at the same time and their integrated impact determines the state of human health as a holistic complex phenomenon.The attention is focused on the system of educational influences of the implementation of mental and spiritual components through the perspective of the school subject «Fundamentals of Health».